Postpartum weight retention among women in Rio de Janeiro: a follow-up study - Kac Gilberto; D'Aquino Benicio Maria Helena; Valente Joaquim Gonçalves; Velásquez-Meléndez Gustavo (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2003)
This study presents follow-up results on trends in postpartum weight retention among women in the city of Rio de Janeiro, Brazil, at 0.5, 2, 6, and 9 months postpartum. The outcome variable, weight retention, was calculated by subtracting the reported pre-pregnancy weight from the observed weight at each interview. Statistical analyses used means and a 95% confidence interval for weight retention. Mean weight retention was 4.7, 4.1, 3.4, and 3.1kg at 0.5, 2, 6 and 9 months postpartum, respectively. At completion of the study, the largest weight retention was observed in women over 30 years of age (4.2kg) and with 30% or more of body fat (5.9kg). The rate of reduction in weight retention was 0.4kg/month, 0.2kg/month, and 0.1kg/ month for the periods 0.5-2, 2-6, and 6-9 months, respectively. The largest reductions were observed among young, single women and those with < 30% of body fat at baseline. The results suggest that variables such as age, parity, schooling, and body fat may be important predictors of postpartum weight retention.